On nonpolynomial monotonicity‐preserving C1 spline interpolation. Issue 4 (7th April 2021) - Barrera, Domingo; Eddargani, Salah; Lamnii, Abdellah; Oraiche, Mohammed
Abstract: New C 1 cubic Hermite interpolation methods based on algebraic trigonometric (AT) spline functions are proposed. In the first one, values of a function and its first derivatives are interpolated. In the second one, a C 1 AT‐spline of low degree which preserves the monotonicity of the given data is defined by adding additional knots. Numerical examples are provided to show the good performance of both interpolation schemes.